2011 International Conference on Networking, Sensing and Control 2011
DOI: 10.1109/icnsc.2011.5874942
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the National Concept Traffic Management for mass evacuation in the Netherlands

Abstract: It is impossible to execute a complete and total preventive evacuation of coastal areas in the Netherlands within the available 48-hour time span in case of a storm surge [1,2]. This is mainly due to the limitations of the road capacity in proportion to the number of inhabitants in the threatened area. A flexible triage is proposed to set the target areas and target groups for those circumstances where it is impossible to evacuate all. The routing of all highway traffic (evacuation as well as not-evacuation) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Specifically related to evacuation, Friso et al (19,20) considered ramp closures in the Netherlands. They divided the study area into three zones for flooding evacuation: (a) threatened area, (b) transit zone, and (c) the rest of the Netherlands.…”
Section: Ramp Closures Under Varying Budgets and Demand Scenariosmentioning
confidence: 99%
“…Specifically related to evacuation, Friso et al (19,20) considered ramp closures in the Netherlands. They divided the study area into three zones for flooding evacuation: (a) threatened area, (b) transit zone, and (c) the rest of the Netherlands.…”
Section: Ramp Closures Under Varying Budgets and Demand Scenariosmentioning
confidence: 99%
“…This 20% estimate is based on an enquiry by “TNS NIPO” in the Netherlands and on what has been learned from experience during hurricane‐induced evacuation in New Orleans . These reference scenarios are described in detail in other research …”
Section: Case Study: Mass Evacuation For the Netherlandsmentioning
confidence: 99%
“…(3,4,18) The need to take alternative strategies for preventive evacuation into account is addressed in recent literature. A comparison of the available time from an early warning to the required time for evacuation in the Netherlands (19,1) as well as an analysis of 50 years of flash flooding in Australia (20,14) showed that preventive evacuation is not always the best strategy to save more lives than other strategies, such as vertical evacuation or staying in situ. This research concludes that literature about vertical evacuation or staying in situ is limitedly available because preventive evacuation is such a well-established means of emergency management.…”
Section: Introductionmentioning
confidence: 99%